Syntactical Morphological Histories Analysis on Top-Down Planned and Self-organised Street Networks of Old City Cores: The Case of Zurich Kreis 1 and Shichaha. - Zhou, Mengru; Axhausen, Kay W.; Wei, Hanbin; Bian, Lanchun (Taylor & Francis, 2021)
Streets in old city cores not only have important transport and social interaction functions but also reveal the laws of urban and cultural development in a region. Space syntax can improve historians’ understanding of how changes in the shape of habitable space affected people’s lives and urban culture in particular times and places by offering a quantitative description of street patterns; here of two old city cores. The study selects the Altstadt of Zurich (the old city of Zurich) and the Shichahai historical district in Beijing, which have a long history and distinctive street patterns. First, this study digitised the historical maps into axis maps. Then, the study described the characteristics of the syntactic evolution of street networks in two cores over four different development stages. Subsequently, a comparative study of the evolution of different syntactic indicators in the two cases was conducted. Finally, it is concluded that although Shichahai and Altstadt are examples of top-down planned and self-organising areas, their street networks have a similar development trend. However, in their evolution, they show greater differentiation.
Keywords: Altstadt; Historische Stadt; Straßennetz; Stadtgeschichte; Stadtstruktur; Historische Entwicklung